Pterostilbene Effect on Inflammatory and Oxidation Markers in Benign Prostatic Hyperplasia Rats Model - Mohammed Ridha Jawad,; Ghaith Ali Jasim, (Iraqi Journal of Pharmaceutical Sciences, 2024)
Pterostilbene is a potent anti-inflammatory and antioxidant used to treat benign prostatic hyperplasia, which is brought on by the induction of testosterone propionate. The objective of the current experiment was to assess the efficacy of pterostilbene treatment in comparison to finasteride and resveratrol by tracking various inflammatory and oxidative markers in a male rat with lower urinary tract symptoms consistent with benign prostatic hyperplasia. The forty-eight male rats were divided into sex groups: the control group, which included eight rats given oil vehicle subcutaneously for 42 days; the induction group, which included eight rats given testosterone propionate(4mg/kg/day) subcutaneously daily dose for fourteen days; and the finasteride group, which included eight rats given finasteride 0.44 mg/kg orally for twenty-eight days after induction Benign prostatic hyperplasia , and the Pterostilbene group, which consisted of 8 rats, got Pterostilbene 200 mg/kg administered orally for 28 days after 14 day Benign prostatic hyperplasia induction, and the other group, which consisted of 8 rats, received Pterostilbene at a dose of 100 mg/kg Use oral gavage to provide 100 mg/kg for the same time period. While the Resveratrol group, which received 100 mg/kg of resveratrol orally. During the identical time frame after Benign prostatic hyperplasia Induction. There were significant differences in the tissue levels of inflammatory markers and oxidative markers Tumor necrosis factor alpha and Glutathione-peroxidase & Malondialdehyde when comparing the pterostilbene 200 group to the induction group (P ≤0.05).Pterostilbene has potent antioxidant and anti-inflammatory properties that help to lessen the growth of the benign prostatic hyperplasia that testosterone propionate causes.